2001
DOI: 10.1007/bf02345143
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the layered compressive properties of trypsintreated articular cartilage: An ultrasound investigation

Abstract: An ultrasound-compression system has been developed for the study of the layered biomechanical properties of articular cartilage. Cartilage specimens harvested from the bovine patella groove, with and without trypsin digestion, were tested using this system. It was noted that a large ultrasound reflection can be detected in the interface of the trypsin digestion front. This ultrasound reflection signal was used to differentiate the deformations of different portions of the cartilage throughout its depth when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
45
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…Quantitative assessment of the softening of artC is of vital importance for preventing OA and evaluating the progress of cartilage regeneration. Various kinds of non-invasive imaging techniques, including diffraction-enhanced x-ray (Mollenhauer et al 2002), microscopic MRI (Xia et al 2001) and ultrasound (US) (Zheng et al 2001), have been emerged to provide visual diagnosis of artC in the past decade. However, these techniques are not able to indicate the early degeneration of artC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative assessment of the softening of artC is of vital importance for preventing OA and evaluating the progress of cartilage regeneration. Various kinds of non-invasive imaging techniques, including diffraction-enhanced x-ray (Mollenhauer et al 2002), microscopic MRI (Xia et al 2001) and ultrasound (US) (Zheng et al 2001), have been emerged to provide visual diagnosis of artC in the past decade. However, these techniques are not able to indicate the early degeneration of artC.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al (2001) developed an US-compression system (50 MHz) to investigate the layered biomechanical properties of artC. It was revealed that the compressive moduli of digested and undigested artCs were significantly different.…”
Section: Introductionmentioning
confidence: 99%
“…27 Elastography of artery walls has been reported using intravascular ultrasound backscattered 28 signals (~30 MHz) obtained while cyclic blood pressure applied a temporally varying loading 29 source on the vessel (de Korte et al 1997Korte et al , 2002. In other tissues, requiring an external compression 30 source, attempts have been made to acquire high frequency (50 MHz) ultrasound signals while 1 squeezing tissue through a slit (2.6mm in width) in a compressor (Cohn et al 1997a, b using a probe with an in-series ultrasound transducer (frequency ranged from 5 to 15 MHz) and a 8 load sensor, Zheng and coworkers have developed a number of systems for ,mapping one-9 dimensional mechanical properties of articular cartilage (AC) using high frequency ultrasound (20 10 to 50 MHz) (Zheng et al 1998(Zheng et al , 2001(Zheng et al , 2002(Zheng et al , 2003. The 2D high-frequency ultrasound elastography 11 using axial compression has only been described in theory or using computer simulation in the 12 literature (Konofagou et al 2001, Righetti et al 2002, 2003.…”
mentioning
confidence: 99%
“…The speed of 9 sound in articular cartilage has been reported to be depth-dependent (Patil et al 2004). Since the 10 stiffness of the cartilage tissues is depth-dependent as well (Schinagl et al 1996, Zheng et al 2001, 11 2002, the cartilage will be deformed non-uniformly under compression. A softer layer contributes 12 more for a certain overall deformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation